An investigation of the effect of athletes` age on the coaching behaviours of professional top-level youth soccer coaches - Partington, M.; Cushion, C.; Harvey, S. (Journal of Sports Sciences, 2014)
The aim of the study was to investigate the behaviours, cognitive processes and practice activities of 12 English youth professional soccer coaches across 6 different age groups. Systematic observation data were collected using a modified version of the Coach Analysis and Intervention System which provided a detailed analysis of coaching behaviours performed during practice. Interpretive interviews were then triangulated with the behavioural data to identify the cognitive processes underlying the behaviours performed. The behavioural results showed that the coaches of the younger age groups used more instruction and the coaches of the older age groups used more divergent questioning and significantly more total feedback and punitive behaviours. The coaches of the younger age groups used more training form activities than the coaches of the older age groups who used more playing form activities. However, the interviews revealed that instead of the age of athletes` directly affecting the cognitive process of coaches it was in fact the coaches underlying beliefs about coaching, their previous experiences and perceived pressures from the context that determined the behaviours performed.